1269The SADS heart of the matter: a review of the sudden arrhythmic death syndrome (SADS) biobank - the cornerstone of a national strategy. (18th June 2020) - Carron, J; O"brien, J; Heverin, K; Gallagher, M; Fitzgibbon, M; Fabre, A; Mcgorrian, C; Galvin, J
Abstract: Background: Sudden cardiac death (SCD) in the young (age 1-35) is commonly attributed to structural and arrhythmogenic syndromes, for which there is often an underlying genetic basis. Expert recommendation emphasises the importance of genetic testing in such cases, however to date this remains the first and only national programme in Europe to facilitate this. Aim: To review detection rates of genetic variants in samples tested via the SADS BioBank and possibly demonstrate the merits of this novel resource for primary prevention for family members. Methods: Family screening and consent for genetic testing was carried out in the Family Heart Screening Clinic. Result analysis of samples sent for molecular autopsy via the BioBank from its induction in January 2015 was performed. Genetic analysis was conducted via the same internationally accredited next generation sequencing lab. Results: From January 2015 to July 2019, 161 samples had been stored in the SADS BioBank following confirmed SADS death on autopsy; 33% female and 67% male. Of these, 24 (14.9%) samples were sent for genetic testing: 21 for a 380 gene molecular autopsy and 3 for a targeted hypertrophic cardiomyopathy panel (173 genes). Of 24 samples tested, 10 (42%) yielded positive genetic variants: 4 American College of Medical Genetics (ACMG) Class IV or V mutations considered pathogenic, and 6 ACMG class III variants of uncertain significance (VUS). Familial cascade screening following confirmed pathogenic mutations resulted in detection of 3 (33.3%) positive genotypes in 9 first-degree relatives. Screening of relatives of Class III positive probands resulted in diagnosis of an Inherited Cardiac Condition (ICC) in 25% of first-degree relatives. 8.2% of first-degree relatives of probands with negative gene testing were given an ICC diagnosis following clinical screening. Conclusions: This short study demonstrates the unique potential the SADS BioBank has to offer in terms of identifying those most at risk and optimising prevention strategies for relatives, thus highlighting the role for such a resource in terms of preventative screening in the future.